2020
DOI: 10.1180/mgm.2020.25
|View full text |Cite
|
Sign up to set email alerts
|

Oxybismutomicrolite, a new pyrochlore-supergroup mineral from the Malkhan pegmatite field, Central Transbaikalia, Russia

Abstract: Oxybismutomicrolite, ideally [(Bi3+,#)2]Σ4+Ta2O6O, where # = subordinate substituents, such as Na+, Ca2+ and vacancy (□), is a microlite-group, pyrochlore-supergroup mineral discovered at the Solnechnaya (‘Sunny’) pegmatite vein, Malkhan pegmatite field, Zabaykalskiy Kray, Central Transbaikalia, Russia. It forms rough octahedral crystals up to 1 mm across and equant grains up to 2 mm across embedded in an albite–lepidolite–elbaite complex. Other associated minerals are Bi-rich fluornatromicrolite, bismutotanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…Excluding synthetic oxy-compounds with a pyrochlore-type structure, well-studied natural pyrochlore-group minerals with O at the Z site are rare. Examples are ‘stibiobetafite’ from pegmatititic Vežná serpentinite, Czech Republic (Černý et al , 1979), ‘uranbetafite’ from foid-bearing syenite ejectum in pyroclastic rock, Vico volcanic complex, Italy (Cámara et al , 2004), pyrochlore from calcite–magnetite–forsterite phoscorite, Kovdor plutonic complex (Ivanyuk et al , 2018) and oxybismutomicrolite from granitic pegmatite, Malkhan, Central Transbaikalia, (Kasatkin et al , 2020) where compositional and single-crystal X-ray diffraction data suggest O dominance in the Z site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excluding synthetic oxy-compounds with a pyrochlore-type structure, well-studied natural pyrochlore-group minerals with O at the Z site are rare. Examples are ‘stibiobetafite’ from pegmatititic Vežná serpentinite, Czech Republic (Černý et al , 1979), ‘uranbetafite’ from foid-bearing syenite ejectum in pyroclastic rock, Vico volcanic complex, Italy (Cámara et al , 2004), pyrochlore from calcite–magnetite–forsterite phoscorite, Kovdor plutonic complex (Ivanyuk et al , 2018) and oxybismutomicrolite from granitic pegmatite, Malkhan, Central Transbaikalia, (Kasatkin et al , 2020) where compositional and single-crystal X-ray diffraction data suggest O dominance in the Z site.…”
Section: Discussionmentioning
confidence: 99%
“…Application of the current pyrochlore nomenclature and classification (Atencio et al , 2010; Christy and Atencio, 2013) revealed several problems associated with the new mineral names (e.g. Mitchell, 2015; Kasatkin et al , 2020). For example, all analytical data obtained during this investigation correspond to an ideal pyrochlore formula (CaNa)Nb 2 O 6 F (Table 1), which, ironically, is not considered by either Atencio et al (2010) or Christy and Atencio (2013).…”
Section: Samples and Methodsmentioning
confidence: 99%
“…These minerals include bismutocolumbite (Peretyazhko et al, 1992), borocookeite (Zagorsky et al, 2003), oxybismutomicrolite (Kasatkin et al, 2020) and nioboixiolite-(Mn 2+ ) (Chukanov et al, 2023).…”
Section: Occurrencementioning
confidence: 99%
“…Oxybismutomicrolite ( Kasatkin et al, 2020 ), (Bi, #) 2 Ta 2 O 6 O, Fd m, a 10.475 (1) Å, V 1149.38 Å 3 . IMA number: 2019-047.…”
Section: Microlite Groupunclassified